The Future of Homoeopathy in India: A Vision for Healing and Harmony (Homoeopathy for All, 2025)
Homoeopathy, a science known for its  gentle healing and holistic approach,  has come a long way in India from being introduced by foreign  missionaries in the 19th century to  being regulated and promoted by  the Government of India in the 21st century. Today, under the dynamic  leadership of Prime Minister Shri  Narendra Modiji India is witnessing  a powerful resurgence of traditional  and integrative medicine systems,  including Homoeopathy, through  the Ministry of AYUSH. This article presents a reflection  on the journey of homoeopathy  in India, but more importantly, it  looks ahead-with confidence and  optimism-towards a future where  homoeopathy plays a central role in  the nation's public health, research,  education, and global outreach.
Keywords: dynamic leadership; global outreach; acknowledged worldwide; digital empowerment